2008
DOI: 10.1143/jjap.47.2468
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Barrier Metal Sputtering on Physical and Chemical Damages in Low-k SiOCH Films with Various Hydrocarbon Content

Abstract: Impact of barrier metal sputtering on physical and chemical damages in the low-k SiOCH films is investigated. In RF sputtering system, the potential drop across the anode sheath accelerates the ion in the plasma toward the wafer surface, inducing damages in the low-k SiOCH dielectrics. High DC bias on the target reduces the anode sheath voltage to suppress the process-induced damage in the SiOCH films. For conventional rigid and porous SiOCH films with methyl (-CH 3 ) additives, the accelerated ions break the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…N. Inoue et al also observed the k value increase from original 2.6 to 3.0 after adding Ta sputtering process with low DC bias. 21 These results indicate that introducing an ultrathin Al 2 O 3 film to pretreat the low k surface does not have a significant impact on the effective k value of the resulting capacitor structure.…”
mentioning
confidence: 81%
“…N. Inoue et al also observed the k value increase from original 2.6 to 3.0 after adding Ta sputtering process with low DC bias. 21 These results indicate that introducing an ultrathin Al 2 O 3 film to pretreat the low k surface does not have a significant impact on the effective k value of the resulting capacitor structure.…”
mentioning
confidence: 81%
“…This process flow specifically consisted of plasma cleaning, physical vapor deposition (PVD), chemical mechanical planarization (CMP) and wet chemical cleaning steps that have all shown the potential to remove terminal organic groups from the matrix of nanoporous organosilicate dielectrics in a similar fashion as observed previously by the pattern transfer process [31,5253]. This is clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 83%
“…To further strengthen the observed chemical structure–mechanical property relationship, the silylated nanoporous organosilicate fins were exposed to additional plasma and wet chemical processes to fill the spaces between the fins with Cu as in a typical state-of-the-art metal interconnect structure. This process flow specifically consisted of plasma cleaning, physical vapor deposition (PVD), chemical mechanical planarization (CMP) and wet chemical cleaning steps that have all shown the potential to remove terminal organic groups from the matrix of nanoporous organosilicate dielectrics in a similar fashion as observed previously by the pattern transfer process [ 31 , 52 53 ]. This is clearly shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1. However, the near continuous implementation of new lowk dielectrics with each new technology was not without significant and well documented challenges [107][108][109][110][111] that severely impacted the development of the associated metallization, [112][113][114] patterning, [115][116][117][118][119] and packaging [120][121][122][123] processes needed to fabricate a high yielding metal interconnect. By the mid 2010's, the challenges of implementing new low-k SiOCH ILDs with k ≤ 2.3 had reached a breaking point relative to overall technology development goals for numerous reasons.…”
Section: The End Of Permittivity Scaling?mentioning
confidence: 99%